Viver e pensar criativamente em tempos de pandemia: repercussões de uma proposta extensionista de desenvolvimento pessoal na UNIPAMPA - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work consists of a research on the repercussions of the work of the author Alfonso López Quintás in an extension project of the Campus Bagé of the Federal University of Pampa, called “Study Group Thinking and Living Creatively”. His pedagogical proposal understands that human development happens through creativity and, as such, he sees man as an encounter being, he conceptualizes all the assumptions for man to access creativity in work and personal life. Based on this proposal, the pilot Group for this extension project was created in 2020, and, in 2021, the first study group happened. The synchronous meetings were weekly in remote format, in which the pedagogical and human development proposal oriented by the author was discussed and studied. In this context, the research had as general objective to describe the perceptions of the project participants, in order to adapt the extensionist methodological practices developed to generate better conditions in the offer of the extension project for the participants of the next editions. Thus, the data generated during the registration period of this project were interpreted in relation to the number of subscribers versus effective participants in the first group meeting, formation areas, workplace, and location. A diagnosis of the intermediate perceptions of the project participants during its course was also performed in order to establish comparisons with the final perceptions at the end of the project. The results of this comparison indicated that the participants' perceptions were maintained at the two data collection moments. Qualitative data generated two analytical categories regarding the impact of the project on the participants, namely: “action/relation” and “self-knowledge”. Some quantitative aspects evaluated allowed the executing team to adjust for the second edition of the group, regarding interaction and self-evaluative questionnaire for each lesson. Based on the contribution of this research, the extension actions of the Study Group analyzed will be further qualified.
Keywords: Percepções; Encontro; Criatividade; Extensão; Perceptions; Encounter; Creativity; Extension; CNPQ::CIENCIAS EXATAS E DA TERRA